Low-Rh high-efficiency three-way catalyst and preparation method thereof
By painting valuable metals on partitions on the catalyst carrier, combined with specific oxide materials, the problem of uneven distribution of precious metals and insufficient catalytic activity has been solved, and catalysts with low RH content and high -efficiency conversion capabilities have met strict regulations.
Patent Information
- Application Number
- CN202411451773.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-21
AI Technical Summary
While the existing catalysts reduce the Rh content, the distribution of precious metals is uneven, resulting in low catalytic activity and pollutant conversion rates, which cannot meet strict regulations and standards.
Using low RH high-efficiency three-effect catalysts, scratch, pupae, and platinum are coated by zoning on the ceramic carrier of the green stone honeycomb, and the catalytic activity of the oxidation nano-nano and aluminum oxide is used Aluminum improves the heat stability of PT.
The catalyst achieves low Rh content and high-efficiency conversion capabilities, and has good conversion effects on CO, CH4 and NOx. The catalyst has a low ignition temperature for CH4 and good durability.
Smart Images

Figure BDA0005089345630000081 
Figure BDA0005089345630000091 
Figure HDA0005089345640000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts, and in particular relates to a low-Rh high-quality three-way catalyst and a preparation method thereof. Background Art
[0002] With the implementation of the National VI Regulations on Natural Gas, the limits of methane and nitrogen oxides have been lowered simultaneously, and the amount of byproduct NH3 generated is particularly stringent. The active component Rh (rhodium) has a strong selective catalytic ability for NO and NH3. In order to meet regulatory standards, the use of active component Rh is essential. However, the expensive price of precious metal Rh leads to high production costs, so reducing the Rh content is one of the key points of catalyst research. In addition, the preparation method of traditional catalysts simply mixes the precious metals platinum, palladium and rhodium or separates the precious metals platinum, palladium and rhodium. Simple coating will lead to uneven distribution of precious metals and low utilization of precious metals, and it is impossible to achieve the ability to improve the conversion rate of pollutants. Summary of the invention
[0003] In view of this, the object of the present invention is to provide a low-Rh high-efficiency three-way catalyst and a preparation method thereof, wherein the three-way catalyst has a low ignition temperature, good durability and good catalytic activity.
[0004] The present invention provides a low-Rh high-efficiency three-way catalyst, using a cordierite honeycomb ceramic carrier as a carrier;
[0005] The upper half of the air inlet end of the carrier is provided with a coating containing rhodium, and the lower half of the air inlet end is provided with a coating containing palladium; the air outlet end of the carrier is provided with a coating containing platinum;
[0006] The rhodium-containing coating includes rhodium, cerium oxide nanowires and cerium zirconium aluminum oxide; the palladium-containing coating includes palladium, lanthanum-modified γ-alumina and cerium zirconium oxide;
[0007] The platinum-containing coating comprises platinum and lanthanum-modified γ-alumina.
[0008] The schematic diagram of the low Rh high-efficiency three-way catalyst zone coating provided by the present invention is as follows Figure 1As shown; the present invention distributes the precious metals Pt, Pd, and Rh at different positions of the catalyst, loads Rh on cerium oxide nanowires and cerium zirconium aluminum oxide with high sensitivity, activity, and oxygen storage capacity, and uses Pt to replace part of Rh, thereby further reducing the Rh content in the catalyst on the basis of improving the utilization rate of Rh. The Rh layer at the inlet end has a strong selectivity for NO, and the precious metal Rh is loaded on a mixture of cerium oxide nanowires and cerium zirconium aluminum oxide with high sensitivity, activity, and oxygen storage capacity. On the one hand, the cerium oxide nanowires can improve the catalytic activity of Rh, and on the other hand, the cerium zirconium aluminum oxide can prevent Rh from forming an alloy with lanthanum-modified γ-alumina and affecting the catalytic activity. The Pt layer at the outlet end has a strong catalytic ability for NO and can replace part of the Rh function. The precious metal Pt is loaded on lanthanum-modified γ-alumina with high thermal stability, which improves the thermal stability of Pt. The three-way catalyst with low Rh and high efficiency prepared by double-layer partition coating improves the catalytic conversion ability of the catalyst and has a high efficiency for CO, CH4, and NO x It has a very good conversion effect, the catalyst has a low ignition temperature for CH4 and good durability.
[0009] The low Rh high-efficiency three-way catalyst provided by the invention uses a cordierite honeycomb ceramic carrier as a carrier; the cordierite honeycomb ceramic carrier has a mesh number of 400 to 600 meshes and a wall thickness of 3 to 6 mils.
[0010] The low Rh high-efficiency three-way catalyst provided by the present invention comprises a coating containing rhodium, and the upper half of the inlet end of the carrier is provided with a coating containing rhodium; the coating containing rhodium comprises rhodium, cerium oxide nanowires and cerium zirconium aluminum oxide. The mass ratio of the cerium oxide nanowires and the cerium zirconium aluminum oxide is 1:2 to 2:1; in a specific embodiment, the mass ratio of the cerium oxide nanowires and the cerium zirconium aluminum oxide is 1:1, 1:2 or 2:1. In the present invention, the cerium oxide nanowires and the cerium zirconium aluminum oxide are both used as specific types of oxygen storage materials, and are mixed to load metal rhodium; the cerium oxide nanowires can improve the catalytic activity of Rh; the cerium zirconium aluminum oxide can prevent Rh from forming an alloy with lanthanum-modified γ-alumina and affecting the catalytic activity.
[0011] The cerium-zirconium-aluminum oxide of the present invention contains 30-60wt% cerium, 10-40wt% aluminum and the balance zirconium.
[0012] The cerium oxide nanowires described in the present invention are prepared according to the following method:
[0013] A strong base, a precipitant, a cerium salt precursor and water are mixed and subjected to a hydrothermal reaction, and then solid-liquid separation and calcination are performed to obtain cerium oxide nanowires; the temperature of the hydrothermal reaction is 80-180° C. and the time is 2-7 hours.
[0014] The strong base is sodium hydroxide with a concentration of 6-12 mol / L; the precipitant is urea, and the molar ratio of urea to cerium ions in the cerium salt precursor is 1-50:1. In the present invention, the cerium salt precursor is selected from cerium nitrate solution; the concentration of cerium nitrate solution is 0.4-0.6 mol / L.
[0015] The low Rh high-efficiency three-way catalyst provided by the present invention comprises a palladium-containing coating, and the lower half of the inlet end of the carrier is provided with a palladium-containing coating; the palladium-containing coating comprises palladium, lanthanum-modified γ-alumina and cerium-zirconium oxide. The mass ratio of lanthanum-modified alumina to cerium-zirconium oxide in the palladium-containing coating of the present invention is 1:1.5 to 1.5:1; the molar ratio of cerium to zirconium in the cerium-zirconium oxide is 1:1.5 to 1.5:1.
[0016] The palladium-containing coating of the present invention preferably also includes an additive, which is an oxide containing M, wherein M is selected from one or more of Ce, Zr, Ba, Sr, La, Ti, Pr and Y. The above-mentioned type of oxide containing M can improve the high temperature stability and catalytic performance of palladium.
[0017] The low Rh high-efficiency three-way catalyst provided by the present invention includes a platinum-containing coating, and the upper half of the inlet end of the carrier is provided with a rhodium-containing coating; the rhodium-containing coating includes rhodium, cerium oxide nanowires and cerium zirconium aluminum oxide. The mass ratio of cerium oxide nanowires and cerium zirconium aluminum oxide in the palladium-containing coating of the present invention is 1:1.5 to 1.5:1; the molar ratio of cerium to zirconium in the cerium zirconium oxide is 1:1.5 to 1.5:1. The cerium oxide nanowires used in the present invention can effectively increase the Rh to NO x Conversion ability.
[0018] The low Rh high-efficiency three-way catalyst provided by the present invention comprises a platinum-containing coating, and the gas outlet end of the carrier is provided with a platinum-containing coating; the platinum-containing coating comprises platinum and lanthanum modified γ-alumina; the present invention has a Pt at the gas outlet end for NO x It has strong conversion ability and can further reduce the content of Rh. The precious metal Pt is loaded on lanthanum-modified γ-alumina with high thermal stability, which improves the thermal stability of Pt.
[0019] The low Rh high-efficiency three-way catalyst provided by the present invention has a palladium loading of 1 to 15 g / L, a rhodium loading of 0.01 to 0.5 g / L, and a platinum loading of 1 to 15 g / L. The coating amounts of the above-mentioned noble metals are all the coating amounts of the noble metals in the whole catalyst after drying.
[0020] Along the axial direction of the cordierite honeycomb ceramic carrier, the length ratio of the palladium-containing coating to the rhodium-containing coating is 1:1; the length ratio of the platinum-containing coating to the rhodium-containing coating is 1:1-1:2.
[0021] The coating amount of the palladium-containing coating in the low-Rh high-efficiency three-way catalyst provided by the present invention is 100-200 g / L, the coating amount of the rhodium-containing coating is 100-200 g / L, and the coating amount of the platinum-containing coating is 100-400 g / L; the coating amounts of the above coatings are all the coating amounts of the coatings after drying in the overall catalyst.
[0022] The present invention provides a method for preparing the low Rh high-efficiency three-way catalyst described in the above technical solution, comprising the following method:
[0023] The lanthanum-modified gamma-alumina and cerium-zirconium oxide are mixed with water, ball-milled to a particle size of 4 to 10 μm, and then mixed with palladium nitrate, a salt additive and a thickener to obtain a palladium-containing slurry;
[0024] The cerium oxide nanowires, the cerium zirconium aluminum material and water are mixed, ball-milled to a particle size of 4 to 10 μm, and then mixed with rhodium nitrate and a thickener to obtain a rhodium-containing slurry;
[0025] The lanthanum-modified γ-alumina material is mixed with water, ball-milled to a particle size of 4 to 10 μm, and then mixed with platinum nitrate, a salt additive and a thickener to obtain a platinum-containing slurry;
[0026] The palladium-containing slurry, the rhodium-containing slurry and the platinum-containing slurry are coated on the cordierite honeycomb ceramic carrier in a negative pressure coating manner, and then dried and calcined to obtain a low-Rh high-efficiency three-way catalyst.
[0027] The method provided by the invention has a simple coating process and reduces production costs.
[0028] The present invention mixes cerium zirconium oxide, lanthanum modified γ-alumina and water, ball-mills them to a particle size of 4 to 10 μm, and then mixes them with palladium nitrate, a salt additive and a thickener to obtain a palladium-containing slurry. The solid content of the mixed slurry after the cerium zirconium oxide, lanthanum modified γ-alumina and water in the present invention is 25 to 35%, preferably 28 to 32%; in a specific embodiment, the solid content is 30%. The salt additive in the present invention can improve the high temperature stability and catalytic performance of the catalyst; the salt additive is selected from one or more nitrates corresponding to the elements Ce, Zr, Ba, Sr, La, Ti, Pr or Y; more preferably barium hydroxide. In a specific embodiment, the mass content of the salt additive is 10%. The thickener in the present invention is selected from hydroxyethyl cellulose and / or hydroxymethyl cellulose; the thickener accounts for 0.8 to 1.5 wt% of the palladium-containing slurry, preferably 1 to 1.5 wt%.
[0029] The present invention mixes cerium oxide nanowires, cerium zirconium aluminum materials and water, ball-mills them to a particle size of 4 to 10 μm, and then mixes them with rhodium nitrate and a thickener to obtain a rhodium-containing slurry. The salt additive in the rhodium-containing slurry accounts for 1 to 15% of the total mass of the cerium oxide nanowires, cerium zirconium aluminum materials and zirconium nitrate; the types of the salt additives and thickeners in the rhodium-containing slurry are the same as those in the palladium-containing slurry, and are not described here. In a specific embodiment, the mass ratio of the cerium oxide nanowires to the cerium zirconium aluminum materials is 1:1, 1:2 or 2:1.
[0030] The present invention mixes lanthanum-modified γ-alumina and water, ball-mills them to a particle size of 4 to 10 μm, and then mixes them with platinum nitrate, a salt additive and a thickener to obtain a platinum-containing slurry. The salt additive in the platinum-containing slurry accounts for 1 to 15% of the total mass of the lanthanum-modified γ-alumina and platinum nitrate. The types and ranges of the salt additive and the thickener in the platinum-containing slurry are the same as those of the salt additive and the thickener in the palladium-containing slurry, and are not repeated here.
[0031] The invention adopts a negative pressure coating method to coat a cordierite honeycomb ceramic carrier with a palladium-containing slurry, a rhodium-containing slurry and a platinum-containing slurry in different areas, and then calcines the obtained catalyst after drying to obtain a low-Rh high-efficiency three-way catalyst.
[0032] The present invention adopts a negative pressure coating machine for coating; the pressure of the negative pressure coating method is -20 to -80 KPa. The present invention performs drying and baking after each coating; the drying temperature is 80 to 150°C, the drying time is 5 to 6 hours; the baking temperature is 500 to 650°C, and the baking time is 2 to 3 hours.
[0033] The catalyst prepared by the method provided by the present invention has a highly efficient purification effect, effectively reduces the emission of pollutants, has a simple preparation method and a simple coating process, and reduces production costs.
[0034] The present invention provides a low-Rh high-efficiency three-way catalyst, which uses a cordierite honeycomb ceramic carrier as a carrier; the upper half of the air inlet end of the carrier is provided with a rhodium-containing coating, and the lower half of the air inlet end is provided with a palladium-containing coating; the outlet end of the carrier is provided with a platinum-containing coating; the rhodium-containing coating includes rhodium, cerium oxide nanowires and cerium zirconium aluminum oxide; the palladium-containing coating includes palladium, lanthanum-modified γ-alumina and cerium zirconium oxide; the platinum-containing coating includes platinum and lanthanum-modified γ-alumina. The present invention enhances the thermal stability of Pt and improves the resistance of Pt and Rh to NO by coating the precious metals rhodium, palladium and platinum on the cordierite honeycomb ceramic carrier in different regions, and then loading the precious metal active components on a specific type of carrier. x Catalytic activity, Pt, Pd catalytic activity for CO, CH4; the catalyst has low Rh content and is very active for CO, CH4 and NO x It has a very good conversion effect, the catalyst has a low ignition temperature for CH4 and good durability. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 A schematic diagram of double-layer partition coating of a low-Rh high-efficiency three-way catalyst provided by the present invention;
[0036] Figure 2 This is a SEM image of cerium oxide nanowires prepared in Example 1 of the present invention;
[0037] Figure 3 This is a schematic diagram of a single-layer coating of a three-way catalyst prepared in Comparative Example 7 of the present invention;
[0038] Figure 4 This is a schematic diagram of double-layer coating of a three-way catalyst prepared in Comparative Example 8 of the present invention;
[0039] Figure 5 This is a schematic diagram of the partition coating of the double-layer bottom layer of the three-way catalyst prepared in Comparative Example 9 of the present invention. DETAILED DESCRIPTION
[0040] In order to further illustrate the present invention, a low Rh high quality three-way catalyst and a preparation method thereof provided by the present invention are described in detail below in conjunction with examples, but they should not be construed as limiting the scope of protection of the present invention.
[0041] Example 1
[0042] The steps of preparing cerium oxide nanowires are as follows:
[0043] The hydrothermal preparation process includes the steps of preparation of precursor solution, precipitation, hydrothermal crystallization, filtration, washing, drying and calcination. The specific design process is as follows:
[0044] a) NaOH (40.0 g) and urea (15.0 g) were dissolved in 100 mL of deionized water to prepare a mixed solution, and the mixture was stirred.
[0045] b) slowly dripping 10 mL of cerium nitrate solution (0.5 mol / L) into the mixed solution to form a suspension, and stirring the suspension for 30 minutes;
[0046] c) transferring the suspension into a 150 mL polytetrafluoroethylene-lined stainless steel autoclave and conducting a hydrothermal reaction at 100° C. for 24 h;
[0047] d) cooling the product to room temperature, and washing with deionized water and anhydrous ethanol three times;
[0048] e) drying the product in air at 70° C. for 10 h;
[0049] f) calcining the above product at 750° C. for 4 h to obtain cerium oxide nanowires.
[0050] The preparation method of three-way catalyst A is as follows:
[0051] First formula coating: take alumina material and cerium zirconium material in the same mass ratio and add them into water, the solid content of the slurry is 30%, put the mixed slurry into a ball mill, add palladium nitrate, barium hydroxide and hydroxyethyl cellulose into the mixed slurry after ball milling, adjust the pH value to 6 with glacial acetic acid and stir for 2 hours, the mass content of palladium nitrate is 4.6%, the mass content of barium hydroxide is 10%, and the mass content of hydroxyethyl cellulose is 1%;
[0052] The second formula coating: cerium oxide nanowires and cerium zirconium aluminum materials are added to water in a mass ratio of 1 / 1, and the solid content of the slurry is 30%. The mixed slurry is placed in a ball mill, and rhodium nitrate and hydroxyethyl cellulose are added to the mixed slurry after ball milling. The pH value is adjusted to 6 with glacial acetic acid and stirred for 2 hours. The mass content of rhodium nitrate is 0.06%, and the mass content of hydroxyethyl cellulose is 1%;
[0053] The third formula coating: take lanthanum modified γ-alumina material and add it to water, the solid content of the slurry is 30%, the slurry is placed in a ball mill, platinum nitrate, barium hydroxide and hydroxyethyl cellulose are added to the mixed slurry after ball milling, the pH value is adjusted to 6 with glacial acetic acid and stirred for 2 hours, the mass content of platinum nitrate is 2.3%, the mass content of barium hydroxide is 10%, and the mass content of hydroxyethyl cellulose is 1%;
[0054] The slurry is coated on the catalyst cordierite carrier using a negative pressure coating machine, and the air pressure of the negative pressure coating machine is -50kPa. The lower layer of the air inlet end is the first formula coating 1, the upper layer of the air inlet end is the second formula coating 2, and the air outlet end is the third formula coating 3.
[0055] The coating amounts of the first formulation coating 1 and the second formulation coating 2 are both 114 g / L, and the coating amount of the third formulation coating 3 is 228 g / L, wherein the loading amount of the precious metal Pt is 2.65 g / L, the loading amount of Pd is 2.65 g / L, and the loading amount of Rh is 0.035 g / L; the length ratio of the first formulation coating 1, the second formulation coating 2, and the third formulation coating 3 is 1:1:1.
[0056] Example 2
[0057] The preparation method of cerium oxide nanowires is the same as that in Example 1.
[0058] The preparation method of three-way catalyst B is as follows: the mass ratio of cerium oxide nanowires to cerium zirconium aluminum material in the second formulation is 1 / 2. The remaining steps are consistent with those in Example 1.
[0059] Example 3
[0060] The preparation method of cerium oxide nanowires is the same as that in Example 1.
[0061] The preparation method of three-way catalyst C is as follows: the mass ratio of cerium oxide nanowires to cerium zirconium aluminum material in the second formulation is 2 / 1. The remaining steps are consistent with those in Example 1.
[0062] Comparative Example 1
[0063] The preparation method of three-way catalyst A1 is to replace the cerium oxide nanowires in the second formula with spherical cerium oxide. The remaining steps are the same as those in Example 1.
[0064] Comparative Example 2
[0065] The preparation method of cerium oxide nanowires is the same as that in Example 1.
[0066] The preparation method of three-way catalyst A2 is to replace the cerium zirconium aluminum oxide in the second formula with lanthanum modified γ-alumina. The remaining steps are the same as those in Example 1.
[0067] Comparative Example 3
[0068] The preparation method of cerium oxide nanowires is the same as that in Example 1.
[0069] The preparation method of three-way catalyst A3 is to replace the cerium zirconium aluminum oxide in the second formula with cerium zirconium oxide. The remaining steps are the same as those in Example 1.
[0070] Comparative Example 4
[0071] The preparation method of cerium oxide nanowires is the same as that in Example 1.
[0072] The preparation method of three-way catalyst A4 is to replace the lanthanum-modified γ-alumina in the third formula with a mixture of cerium zirconium oxide and lanthanum-modified γ-alumina (mass ratio is 1:1). The remaining steps are the same as those in Example 1.
[0073] Comparative Example 5
[0074] The preparation method of cerium oxide nanowires is the same as that in Example 1.
[0075] The preparation method of three-way catalyst A5 is to use cerium oxide nanowires as the active carrier in the third formulation. The remaining steps are the same as those in Example 1.
[0076] Comparative Example 6
[0077] The preparation method of nano cerium oxide is the same as that in Example 1.
[0078] The preparation method of three-way catalyst A6 is to use cerium zirconium aluminum oxide as the active carrier in the third formulation. The remaining steps are the same as those in Example 1.
[0079] Comparative Example 7
[0080] Catalyst A7 is coated in a single layer (e.g. Figure 3), the coating amount of the fourth formula coating 4 is 456 g / L, among which the loading amount of the precious metal Pt is 2.65 g / L, the loading amount of Pd is 2.65 g / L, and the loading amount of Rh is 0.035 g / L.
[0081] Fourth formula coating: take alumina material and cerium zirconium material in a mass ratio of 30% and add them into water, the solid content of the slurry is 30%, the mixed slurry is placed in a ball mill, palladium nitrate, platinum nitrate, rhodium nitrate, barium hydroxide and hydroxyethyl cellulose are added to the mixed slurry after ball milling, the pH value is adjusted to 6 with glacial acetic acid and stirred for 2 hours, the mass contents of palladium nitrate, rhodium nitrate and platinum nitrate are 1.15%, 0.015% and 1.15% respectively, the mass content of barium hydroxide is 10%, and the mass content of hydroxyethyl cellulose is 1%;
[0082] Comparative Example 8
[0083] Catalyst A8 adopts double-layer coating method (such as Figure 4 ), the lower layer is the fifth formulation coating 5, and the upper layer is the sixth formulation coating 6.
[0084] The fifth formula coating: take lanthanum modified γ-alumina material and cerium zirconium oxide in a mass ratio of 30% and add them into water, the solid content of the slurry is 30%, the mixed slurry is placed in a ball mill, palladium nitrate, platinum nitrate, barium hydroxide and hydroxyethyl cellulose are added to the mixed slurry after ball milling, the pH value is adjusted to 6 with glacial acetic acid and stirred for 2 hours, the mass contents of palladium nitrate, rhodium nitrate and platinum nitrate are 2.3% and 2.3% respectively, the mass content of barium hydroxide is 10%, and the mass content of hydroxyethyl cellulose is 1%;
[0085] The sixth formulation coating is the same as the second formulation coating in Example 1, except that the content of the precious metal Rh is 0.03%.
[0086] The coating amounts of the fifth formulation coating 1 and the sixth formulation coating 6 are both 228 g / L, wherein the loading amount of the precious metal Pt is 2.65 g / L, the loading amount of Pd is 2.65 g / L, and the loading amount of Rh is 0.035 g / L.
[0087] Comparative Example 9
[0088] Catalyst A9 adopts double-layer bottom layer partition coating method (such as Figure 5 ), the lower layer at the air inlet end is the coating 7 of the first formulation in Example 1, the lower layer at the air outlet end is the coating 8 of the seventh formulation, and the upper layer is the coating 9 of the eighth formulation in Example 1.
[0089] The seventh formulation coating is the same as the third formulation of Example 1, except that the content of precious metal Pt is 4.6%.
[0090] The eighth formulation coating is the same as the second formulation coating in Example 1, except that the content of the precious metal Rh is 0.03%.
[0091] The coating amounts of the first formulation coating 7 and the seventh formulation coating 8 are both 114 g / L, and the coating amount of the sixth formulation coating 9 is 228 g / L, wherein the loading amount of the precious metal Pt is 2.65 g / L, the loading amount of Pd is 2.65 g / L, and the loading amount of Rh is 0.035 g / L. The length ratio of the first formulation coating 7 and the seventh formulation coating 8 is 1:1.
[0092] The catalysts prepared in the examples and comparative examples were evaluated for activity, and the results were as follows:
[0093] The test was carried out in a reactor. Test method: A mixed gas containing NO, CO2, H2O, CH4, CO, O2, and H2 was introduced into a high-temperature reactor, wherein NO: 2000ppm, CO2: 8%, H2O: 10%, CH4: 1000ppm, O2: 0.6%, CO: 7500ppm, and H2: 0.45%; the heating rate was 5℃ / min, and finally the temperature was raised to 650℃. Aging treatment conditions: 10% H2O air atmosphere, aging temperature 850℃, time 20h. The test results of fresh catalysts are shown in Table 1, and the test results of aged catalysts are shown in Table 2.
[0094] Table 1 Evaluation results of fresh catalyst activity
[0095]
[0096]
[0097] T50: The temperature at which the pollutant conversion rate reaches 50%, T90: The temperature at which the pollutant conversion rate reaches 90%.
[0098] As shown in Table 1, the ignition temperatures T50 of CO and CH4 of the fresh catalysts prepared in Examples 1 to 3 are 145°C to 164°C and 318°C to 343°C, respectively, and the T90 of NO is 306°C to 337°C. The ignition temperature of CO is better than that of the comparative catalyst as a whole, and in particular, the complete conversion temperature of NO in Example 1 is significantly lower than that of the comparative example. T50 is the temperature required to achieve a 50% conversion rate, and T90 is the temperature required to achieve a 90% conversion rate, and the complete conversion temperature. The higher the temperature, the worse the performance, and the lower the temperature, the better the performance. It can be seen from Table 1 that the ignition temperatures of catalysts A to C prepared by the preparation method of the present invention are lower and have better catalytic activity.
[0099] Table 2 Activity evaluation results of aged catalysts
[0100] catalyst CO(T50) / ℃ NO(T90) / ℃ <![CDATA[CH4(T50) / ℃]]> A 168 351 358 B 171 365 367 C 187 369 375 A1 195 376 387 A2 215 378 393 A3 201 397 405 A4 192 369 397 A5 232 356 379 A6 221 387 401 A7 332 482 507 A8 245 546 467 A9 223 385 398
[0101] As shown in Table 2, the ignition temperatures T50 of CO, NO and CH4 of the catalysts prepared in Examples 1 to 3 after aging are 168°C to 187°C, 351°C to 369°C and 358°C to 375°C respectively, and their T50 are all lower than those of the comparative catalysts. As shown in Table 2, the catalysts A to C prepared by the preparation method of the present invention not only have lower ignition temperatures, better catalytic activity and stronger durability.
[0102] It can be seen from the above embodiments that the present invention provides a low-Rh high-efficiency three-way catalyst, with a cordierite honeycomb ceramic carrier as the carrier; the upper half of the inlet end of the carrier is provided with a rhodium-containing coating, and the lower half of the inlet end is provided with a palladium-containing coating; the outlet end of the carrier is provided with a platinum-containing coating; the rhodium-containing coating includes rhodium, cerium oxide nanowires and cerium zirconium aluminum oxide; the palladium-containing coating includes palladium, lanthanum-modified alumina and cerium zirconium oxide; the platinum-containing coating includes platinum and lanthanum-modified γ-alumina. The present invention enhances the thermal stability of Pt and improves the reaction of Pt and Rh to NO by coating the precious metals rhodium, palladium and platinum on the cordierite honeycomb ceramic carrier in different areas, and then loading the precious metal active components on a specific type of carrier. x Catalytic activity, Pt, Pd catalytic activity for CO, CH4; the catalyst has low Rh content and is very active for CO, CH4 and NO x It has a very good conversion effect, the catalyst has a low ignition temperature for CH4 and good durability.
[0103] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A low Rh high efficiency three-way catalyst, characterized in that: Using cordierite honeycomb ceramic carrier as carrier; The upper half of the air inlet end of the carrier is provided with a coating containing rhodium, and the lower half of the air inlet end is provided with a coating containing palladium; the air outlet end of the carrier is provided with a coating containing platinum; The rhodium-containing coating includes rhodium, cerium oxide nanowires and cerium zirconium aluminum oxide; the palladium-containing coating includes palladium, lanthanum-modified γ-alumina and cerium zirconium oxide; The platinum-containing coating comprises platinum and lanthanum-modified γ-alumina.
2. The low Rh high-efficiency three-way catalyst according to claim 1, characterized in that: The cerium-zirconium-aluminum oxide contains 30-60% cerium by mole, 10-40% aluminum by mole, and the balance is zirconium; The mass ratio of the cerium oxide nanowires to cerium zirconium aluminum oxide is 1:2 to 2:
1.
3. The low Rh high-efficiency three-way catalyst according to claim 1, characterized in that: The mass ratio of lanthanum-modified γ-alumina to cerium-zirconium oxide in the palladium-containing coating is 1:1.5 to 1.5:1; The molar ratio of cerium to zirconium in the cerium-zirconium oxide is 1:1.5 to 1.5:
1.
4. The low Rh high-efficiency three-way catalyst according to claim 1, characterized in that: The cordierite honeycomb ceramic carrier has a mesh number of 400 to 600 meshes and a wall thickness of 3 to 6 mils.
5. The low Rh high-efficiency three-way catalyst according to claim 1, characterized in that: The loading amount of palladium is 1 to 15 g / L; the loading amount of rhodium is 0.01 to 0.5 g / L; the loading amount of platinum is 1 to 15 g / L; Along the axial direction of the cordierite honeycomb ceramic carrier, the length ratio of the palladium-containing coating layer to the rhodium-containing coating layer is 1:1; The ratio of the length of the platinum-containing coating to the length of the rhodium-containing coating is 1:1 to 1:
2.
6. The low Rh high-efficiency three-way catalyst according to claim 1, characterized in that: The coating amount of the palladium-containing coating is 100-200 g / L, the coating amount of the rhodium-containing coating is 100-200 g / L, and the coating amount of the platinum-containing coating is 100-400 g / L.
7. A method for preparing a low Rh high-efficiency three-way catalyst according to any one of claims 1 to 6, characterized in that: Includes the following methods: The lanthanum-modified γ-alumina material, cerium-zirconium oxide and water are mixed, ball-milled to a particle size of 4 to 10 μm, and then mixed with palladium nitrate, a salt additive and a thickener to obtain a palladium-containing slurry; The cerium oxide nanowires, the cerium zirconium aluminum material and water are mixed, ball-milled to a particle size of 4 to 10 μm, and then mixed with rhodium nitrate, a salt additive and a thickener to obtain a rhodium-containing slurry; The lanthanum-modified gamma-alumina is mixed with water, ball-milled to a particle size of 4 to 10 μm, and then mixed with platinum nitrate, a salt additive and a thickener to obtain a platinum-containing slurry; The palladium-containing slurry, the rhodium-containing slurry and the platinum-containing slurry are coated on the cordierite honeycomb ceramic carrier in a negative pressure coating manner, and then dried and calcined to obtain a low-Rh high-efficiency three-way catalyst.
8. The preparation method according to claim 7, characterized in that: The drying temperature is 80-150°C and the drying time is 5-6 hours; The calcination temperature is 500-650°C and the calcination time is 2-3h; The pressure of the negative pressure coating method is -20 to -80 KPa.
9. The preparation method according to claim 7, characterized in that: The salt additive used in preparing the slurry is selected from one or more nitrates corresponding to the elements Ce, Zr, Ba, Sr, La, Ti, Pr or Y; The salt additive in the palladium-containing slurry accounts for 1 to 15% of the total mass of the lanthanum-modified γ-alumina, cerium-zirconium oxide and palladium nitrate; The salt additive in the rhodium-containing slurry accounts for 1 to 15% of the total mass of the cerium oxide nanowires, the cerium zirconium aluminum material and the zirconium nitrate; The salt additive in the platinum-containing slurry accounts for 1 to 15% of the total mass of the lanthanum-modified gamma-alumina and platinum nitrate.
10. The preparation method according to claim 7, characterized in that: The cerium oxide nanowires are prepared according to the following method: A strong base, a precipitant, a cerium salt precursor and water are mixed and subjected to a hydrothermal reaction, and then solid-liquid separation and calcination are performed to obtain cerium oxide nanowires; The temperature of the hydrothermal reaction is 80-180° C. and the time is 2-7 hours.
Citation Information
Cited By
Tail gas denitration system
CN121775654A